Schutz der Vertragspartner aus § 103 InsO Plädoyer für die Erweiterung des Insolvenzvertragsrechts um neue Institute bei Wertverlusten und Aufwendungen - Hoeg, Elisabeth (Schriften zum Insolvenzrecht, 2023)
This dissertation clarifies a largely unresolved problem about executory contracts in bankruptcy proceedings. Particularly, how to deal with burdens on creditors that arise while waiting for assumption or rejection. It contains an assessment of whether bankruptcy law should be supplemented by new compensation regimes. In doing so, the author draws on all sources available to legal scholars: Legal history, systematic considerations, comparisons within the legal system. A review shows that the procedural burdens have intensified in recent decades. The author recognizes the need for reform and presents a draft law.